Measurements and predictions of wind turbine tower shadow and fairing effects. Issue 179 (August 2018) - Noyes, Carlos; Qin, Chao; Loth, Eric; Schreck, Scott
Abstract: Downwind two-bladed rotor configurations can have advantages in reducing rotor mass for wind turbines, compared with three-bladed upwind designs. However, the tower shadow adds an aerodynamic complication that can be difficult to quantify and predict. This study presents and analyzes a previously unpublished subset of data collected during an extensive wind tunnel campaign, the Unsteady Aerodynamic Experiment (UAE). At high tip speed ratios, the tower shadow is a dominating contributor to bending moment oscillations but can be mitigated by the use of a tower fairing when such a fairing is aligned with the flow. At lower tip speed ratios where the blades can undergo aerodynamic stall and hysteresis, tower shadow was only a secondary contributor to bending moments and the tower fairing did not significantly impact bending moments. The aeroelastic simulation code called FAST was used to predict the same experimental conditions. In general, simulations reasonably predicted most of the cycle-averaged aspects, but only qualitatively predicted the unsteady variations due to tower shadow. To improve simulation predictions inside the tower wake, it is suggested that future work model the unsteady wake component associated with cylinder shedding and to consider a wake model for tower fairings at various wind incidence angles. Highlights: Tower shadow for downwind turbines can be reduced with an aerodynamic fairing. The fairing loses effectiveness when misaligned with the flow. Steady tower shadow models used in simulators do not model the extremes wake effects. Steady tower shadow models can predict average bending moment effects.